Effects of eliminating the US–China trade dispute tariffs - Zheng, Jian; Zhou, Shudong; Li, Xingzi; Padula, Antonio Domingos; Martin, Will (Cambridge University Press, 2023)
This paper examines the economic implications of the tariff increases by the United States and by China during the Trump era trade dispute and the gains from their potential removal. The increases were dramatic, with the US raising tariffs on industrial products by a factor of six – with particularly large tariff increases on intermediate and capital goods – and China increasing its tariffs on US agricultural products more than five-fold. These changes distort trade and production decisions in both countries and undercut the global trading system. They resulted in substantial economic losses to each country, with import volumes reduced by 4.9% in China and 4.5% in the USA, and bilateral trade patterns were massively distorted. Their cost to the United States rose at the end of 2021, when the import expansion provisions of the Trump era Phase One Agreement expired. Negotiating the abolition of these costly and disruptive tariffs would generate substantial real income gains for both countries and help lower US consumer prices.